40Ar/39Ar age and geochemistry of the post-collisional Miocene Yamadag volcanics in the Arapkir area (Malatya Province), eastern Anatolia, Turkey - Kurum, Sevcan; Onal, Ayten; Boztug, Durmus; Spell, Terry; Arslan, Mehmet (Pergamon-Elsevier Science Ltd, 2008)
The Neogene Yamadag volcanics occupy a vast area between Sivas and Malatya in eastern Anatolia, Turkey. These volcanic rocks are characterized by pyroclastics comprising agglomerates, tuffs and some small outcrops of basaltic-andesitic-dacitic rocks, overlain upward by basaltic and dacitic rocks, and finally by basaltic lava flows in the Arapkir area, northern Malatya Province. The basaltic lava flows in the Arapkir area yield a 40Ar/39Ar age of 15.8 +/- 0.2 Ma, whereas the dacitic lava flows give 40Ar/39Ar ages ranging from 17.6 through 14.7 +/- 0.1 to 12.2 +/- 0.2 Ma, corresponding to the Middle Miocene. These volcanic rocks have subalkaline basaltic, basaltic andesitic; alkaline basaltic trachyandesitic and dacitic chemical compositions. Some special textures, such as spongy-cellular, sieve and embayed textures; oscillatory zoning and glass inclusions in plagioclase phenocrysts; ghost amphiboles and fresh biotite flakes are attributable to disequilibrium crystallization related to magma mixing between coeval magmas. The main solidification processes consist of fractional crystallization and magma mixing which were operative during the soldification of these volcanic rocks. The dacitic rocks are enriched in LILE, LREE and Th, U type HFSE relative to the basaltic rocks. The basaltic rocks also show some marked differences in terms of trace-element and REE geochemistry; namely, the alkaline basaltic trachyandesites have pronounced higher HFSE, MREE and HREE contents relative to the subalkaline basalts. Trace and REE geochemical data reveal the existence of three distinct magma sources - one subalkaline basaltic trachyandesitic, one alkaline basaltic and one dacitic - in the genesis of the Yamadag volcanics in the Arapkir region. The subalkaline basaltic and alkaline basaltic trachyandesitic magmas were derived from an E-MORB type enriched mantle source with a relatively high- and low-degree partial melting, respectively. The magmatic melt of dacitic rocks seem to be derived from an OIB-type enriched lithospheric mantle with a low proportion of partial melting. The enriched lithospheric mantle source reflect the metasomatism induced by earlier subduction-derived fluids. All these coeval magmas were generated in a post-collisional extensional geodynamic setting in Eastern Anatolia, Turkey. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: 40Ar/39Ar dating; geochemistry; Yamadag volcanism; eastern Turkey